Follistatins in glucose regulation in healthy and obese individuals. Issue 3 (3rd December 2018) - Perakakis, Nikolaos; Kokkinos, Alexander; Peradze, Natia; Tentolouris, Nicholas; Ghaly, Wael; Tsilingiris, Dimitrios; Alexandrou, Andreas; Mantzoros, Christos S.
Abstract : Aims: It has been suggested recently that follistatin (FST) and its homologous protein, follistatin‐like 3 (FSTL3), may be a therapeutic target in the treatment of type 2 diabetes because of their glucose‐regulatory effects in rodents. Materials and Methods: We investigated this hypothesis in humans by studying the physiology of a possible glycaemia–follistatin feedback loop, that is, whether glucose, but not lipid intake (oral or intravenous), can regulate circulating FST and FSTL3 in healthy humans (n = 32), whether the levels of follistatins change in response to various types of bariatric operation in morbidly obese individuals, with or without type 2 diabetes (n = 41), and whether such changes are associated prospectively with improvement of glucose homeostasis/insulin sensitivity. Results: In healthy individuals, circulating FST decreases after intravenous or oral glucose intake compared to controls, indicating the presence of a negative feedback mechanism. In morbid obesity, insulin resistance, glycaemia, circulating FST and FSTL3 are all reduced (by 22%‐33%) after Roux‐en‐Y gastric bypass (RYGB) and sleeve gastrectomy. Importantly, the changes in circulating FST 3 months after bariatric surgery are associated prospectively with the changes in glucose, insulin, HOMA‐IR and HbA1c observed 6 months postoperatively in individuals with and without type 2 diabetes. Conclusions: Our findings provide evidence of an important role of FST in glucose homeostasis in healthy individuals as well as in severely obese individuals with insulin resistance and type 2 diabetes. Our data extend recent results from animal studies to humans and support the need for further evaluation of FST inactivation strategies for targeting hyperglycaemia and insulin resistance.